Phenotypic and molecular variation among selected Curcuma alismatifolia gagnep. mutants derived from acute and chronic gamma irradiation - Taheri, Sima (2014)
Studies were conducted to study phenotypic and molecular variation among selected Curcuma alismatifolia mutants through acute and chronic gamma irradiation and to develop new variants of C. alismatifolia. In acute gamma irradiation, rhizomes in the sprouting bud stage were irradiated at eight different doses of 0, 10, 20, 25, 35, 40, 60, and 100 Gy. Radiation sensitivity tests revealed that the LD50 of the varieties were achieved at 21 Gy for ‘Chiang Mai Red’, 23 Gy for ‘Sweet Pink’, 25 Gy for ‘Kimono Pink’, and 28 Gy for ‘Doi Tung 554’. From the analysis of variance (ANOVA), significant variations were observed for vegetative traits, flowering development, and rhizome characteristics among the four cultivars of C. alismatifolia and dose levels as well as the dose × variety interaction. In first generation (M1V1), as many as 52 chlorophyll mutants were observed, resulting in a mean mutation frequency of 38.5 % in which 13.1 and 19.3% were produced by 10 and 20 Gy doses, respectively. Individual mutant DT20-1 with twotone purple bract color was the most attractive mutant generated. In SSR analysis,the obtained results indicated the high efficiency of polymorphic SSR loci for genetic studies among treated and non-treated C. alismatifolia individual plants. 20 Gy acutely irradiated individuals showed a higher mean percentage of polymorphic loci (62.5%) than the 10 Gy (59.38%) and non-treated (22%) ones. By HRM analysis, all studied irradiated individual plants produced melting curves with different melting temperature (Tm) from their control individual plants. In chronic gamma irradiation, plants that were exposed to radiation at doses of 14.6, 33, and 87.4 Gy showed significant decreases in the vegetative traits as compared to the controls. Interestingly, low doses of gamma irradiation stimulated the vegetative growth and promoted earlier flowering of mutants compared to controls. However, higher dose rates decreased the flowering capacity and reduced the quality of the rhizomes of C. alismatifolia mutants. In SSR analysis, the overall genetic variability for the varieties studied showed that chronic gamma irradiation particularly at higher dose rates (14.6, 33, and 87.4 Gy) were able to induce more genetic variations to genome of studied C. alismatifolia individual plants. In order to study the morphological and genetic stability of mutants, for both acute and chronic gamma irradiations, studies were continued into the second generation (M1V2). In acute gamma irradiationchlorophyll mutation frequency decreased significantlyat 10 and 20 Gy irradiated plants in M1V2. Individual DT20-1 with two tone purple color at first generation produced solid mutant with deeper purple bracts in M1V2. In order to gain distinctness, uniformity and stability (DUS) of mutants, the rhizomes of all individual plants were grown in M1V3 generation and observations were continued. Nine individual plants with bract color variations and dwarfism were selected for further studies in M1V4 generation.DT20-1 mutant that maintained the deep purple color in M1V3 was considered a desirable potential mutant. SSR analysis in the second generation showed that the percentage of polymorphic loci decreased from 59.3% to 40.6% for 10 Gy individual plants. Similarly, at 20 Gy, percentage of polymorphic loci decreased from 62.5% to 50.0 %. In chronic gamma irradiation, none of the flower shape and color variations observed in first generation were transferred to the next generation. The effects induced by chronic gamma radiation on these plants are more likely to be physiological changes at sublethal dosages rather than irreversible genetic effects. In SSR analysis the average number of alleles, mean Shannon’s information index, and the mean PIC values decreased in second generation as compared to first generation. The percentage of polymorphic loci decreased from 59.38% in M1V1 to 37.5% in M1V2. In conclusion, the above studies demonstrated that the mutation frequencies induced by acute gamma irradiation were higher than that of chronic gamma irradiation. In general, new variants of C. alismatifolia varieties developed in this study have the potential to be introduced to the Malaysian flower industry.